2017
DOI: 10.1590/2179-8087.025015
|View full text |Cite
|
Sign up to set email alerts
|

Ecologia da Paisagem de uma Bacia Hidrográfica dos Tabuleiros Costeiros do Brasil

Abstract: RESUMOO objetivo deste trabalho foi quantificar o uso da terra e as métricas da paisagem da Bacia Hidrográfica do Rio Piauitinga, SE, a partir de imagens orbitais de alta resolução espacial. Foi utilizada uma imagem RapidEye com resolução espacial de 5 metros para mapear o uso e cobertura da terra. Foram consideradas as métricas de ecologia da paisagem ao nível de classe. Além disso, foram realizadas simulações da distância de borda nos fragmentos florestais remanescentes. A bacia apresenta uma paisagem domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
8
0
5
Order By: Relevance
“…According to the area metrics (CA and PLAND), in the B2 area, the Forest and Other uses classes virtually do not show any difference, since the Forest class has 1329.06 hectares, equivalent to 50.61%, and the class of Other uses with 1296.78 ha corresponding to 49.39%, totaling an area of 2625.85 ha. The B2 area has 386 elements, 299 of forest fragments, with mean size of fragments of 4.45 ha, showing values that according to Fernandes et al (2017a) are more susceptible to degradation. In the other hand, the class of Other uses has an average size of 14.91 ha.…”
Section: Resultsmentioning
confidence: 99%
“…According to the area metrics (CA and PLAND), in the B2 area, the Forest and Other uses classes virtually do not show any difference, since the Forest class has 1329.06 hectares, equivalent to 50.61%, and the class of Other uses with 1296.78 ha corresponding to 49.39%, totaling an area of 2625.85 ha. The B2 area has 386 elements, 299 of forest fragments, with mean size of fragments of 4.45 ha, showing values that according to Fernandes et al (2017a) are more susceptible to degradation. In the other hand, the class of Other uses has an average size of 14.91 ha.…”
Section: Resultsmentioning
confidence: 99%
“…Já nos anos de 2004 e 2014 essa métrica diminui ainda mais chegando a 88 e 89 metros respectivamente (Figura 3e). Fernandes et al (2017), analisando a paisagem da bacia do rio Piauitinga, mostrou que as áreas de pastagem possuem menor isolamento em relação as outras classes, com valor de MNN de 24,5 As manchas maiores da classe Agricultura/pasto também se tornaram mais próximas em um contexto geral, chegando a um valor máximo em 2014 (Figura 3f). Em detrimento da expansão agrícola, é possível observar uma maior proximidade entre as manchas de Solo exposto a partir de 1994, tornando mais evidente entre 2004 a 2014, período em que o número de manchas aumentou de modo acentuado.…”
Section: Métricas De Paisagemunclassified
“…Several studies on this theme have been developed in tropical dry forests by applying landscape metrics to quantify their fragmentation (Pang et al, 2010;Pham et al, 2011;Coelho et al, 2014;Schulz et al, 2017;Fernandes et al, 2017;Fischer, 2018), and the results have shown that along with the rapid growth of the pasture/agriculture class, the predominant landscape of natural vegetation is being replaced by an increasingly heterogeneous, less diverse and fragmented vegetation (Fernandes et al, 2017). Therefore, with the premise that over the years, land-use has promoted forest fragmentation, which compromises the conservation of biodiversity.…”
Section: Introductionmentioning
confidence: 99%